ANALISIS INTEGRASI MATERI SEJARAH DAN KEBERAGAMAAN DALAM PRAKTIK PENDIDIKAN DI INDONESIA - Asfar, Khalimatus Sa'diyah; Miftah, Muhammad (Al’ulum Jurnal Pendidikan Islam, 2024)
This research is motivated by Indonesia's long history based on diversity of cultures, languages, religions, ethnicities, races, and customs. The integration of historical and religious materials in educational practices in Indonesia aims to understand the learning content that will shape the character of students as grassroots individuals with a nationalist spirit and religious moral values. In this study, the author employs a qualitative literature approach by collecting various relevant data sources. The theory of multicultural education, consisting of five elements: content integration, understanding the construction process of knowledge, reducing prejudice, equity pedagogy, and strengthening school culture as well as social structure by James A. Banks, serves as the analytical foundation for this research. The results indicate that historical materials also contain teachings on being tolerant and open to various differences in race, ethnicity, tribe, and culture. History learning that incorporates religious practices will create a harmonious environment by applying the principles of mutual respect, equality, and togetherness.